Impact of the COVID-19 pandemic on Black communities in Canada - Kemei, Janet; Tulli, Mia; Olanlesi-Aliu, Adedoyin; Tunde-Byass, Modupe; Salami, Bukola (My University, 2023)
The COVID-19 pandemic has resulted in differential impacts on the Black communities in Canada and has unmasked existing race-related health inequities. The purpose of this study was to illuminate the impacts of the COVID-19 pandemic on Black people in Canada. Historically, social inequalities have determined the impacts of pandemics on the population, and in the case of the COVID-19 pandemic, disproportionate infections and mortalities have become evident among racialized communities in Canada. This qualitative descriptive study utilized an intersectionality framework. We invited Black stakeholders across Canada to participate in semi-structured interviews to deepen our knowledge of the impacts of the COVID-19 pandemic on Black communities in Canada. A total of 30 interviews were recorded, transcribed verbatim, and analyzed using content analysis. Our findings fell into three categories: (1) increased vulnerability to COVID-19 disease, (2) mental impacts, and (3) addressing impacts of the COVID-19 pandemic. The findings show the underlying systemic inequities in Canada and systemic racism exacerbated health inequities among the Black communities and undermined interventions by public health agencies to curb the spread of COVID-19 and associated impacts on Black and other racialized communities. The paper concludes by identifying critical areas for future intervention in policy and practice.
Keywords: COVID-19; Black communities; health inequities